Anglican Communion in crisis : how Episcopal dissidents and their African allies are reshaping Anglicanism - Hassett, Miranda Katherine (Anthropology online., 2007)
The sign outside the conservative, white church in the small southern U.S. town announces that the church is part of the Episcopal Church--of Rwanda. In Anglican Communion in Crisis, Miranda Hassett tells the fascinating story of how a new alliance between conservative American Episcopalians and African Anglicans is transforming conflicts between American Episcopalians--especially over homosexuality--into global conflicts within the Anglican church. In the mid-1990s, conservative American Episcopalians and Anglican leaders from Africa and other parts of the Southern Hemisphere began to forge t.